2011
DOI: 10.3109/09553002.2011.598209
|View full text |Cite
|
Sign up to set email alerts
|

Limitations (and merits) of PENELOPE as a track-structure code

Abstract: PENELOPE can be employed advantageously in some track-structure applications provided that the default model for inelastic interactions of electrons is replaced by suitable tables of differential and total cross sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
0
39
1
Order By: Relevance
“…For radiation interactions with GNPs, Geant4-Penelope is unable to precisely reproduce very low-energy electron interactions in the GNP since it is limited to electrons of energies above 100 eV and neglects the reduced dimensionality of the GNPs, this has been shown in work on nanotubes. 31, 43, 44 Furthermore, the interaction probability per Gray with 6 MV photons in this study was found to be higher than that reported in previous studies 9, 18 . We found that this difference was due to the different physics setting used in the two simulations.…”
Section: Discussioncontrasting
confidence: 77%
“…For radiation interactions with GNPs, Geant4-Penelope is unable to precisely reproduce very low-energy electron interactions in the GNP since it is limited to electrons of energies above 100 eV and neglects the reduced dimensionality of the GNPs, this has been shown in work on nanotubes. 31, 43, 44 Furthermore, the interaction probability per Gray with 6 MV photons in this study was found to be higher than that reported in previous studies 9, 18 . We found that this difference was due to the different physics setting used in the two simulations.…”
Section: Discussioncontrasting
confidence: 77%
“…The remaining parameters control the mixed simulation algorithm for the transport of electrons and positrons. To force detailed (event-byevent) simulation, the latter parameters were set to zero (21).…”
Section: Monte Carlo Simulations: the Penelope Codementioning
confidence: 99%
“…[3][4][5] A dose enhancement from using GNPs in radiotherapy has already been demonstrated using Monte Carlo simulations; 6 however these simulations are of limited accuracy at micrometer scales, as the continuous physics models used to date break down at small spatial resolutions. 7,8 As one moves towards more accurate microdosimetric measurements of the impact of GNPs, discrete physics models become necessary as they improve the spatial resolution in simulation. As the physical effects of GNP boosted radiotherapy occur across energy scales that descend down to 10 eV, Monte Carlo simulations require discrete physics models down to these very low energies in order to avoid underestimating absorbed dose and secondary particle generation.…”
Section: Introductionmentioning
confidence: 99%